The policing of transnational protest - Della Porta, Donatella; Peterson, Abby; Reiter, Herbert (Advances in criminology, 2006)
Policing transnational protest : an introduction / Donatella della Porta, Abby Peterson and Herbert Reiter -- The policing of global protest : the G8 at Genoa and its aftermath / Donatella della Porta and Herbert Reiter -- Policing contentious politics at transnational summits : Darth Vader or the Keystone Cops? / Abby Peterson -- The policing of transnational protest in Canada / Mike King and David Waddington -- Aspects of the "new penology" in the police response to major political protests in the United States, 1999-2000 / John Noakes and Patrick F. Gillham -- Negotiating political protest in Gothenburg and Copenhagen / Mattias Wahlström and Mikael Oskarsson -- Formalizing the informal : the EU approach to transnational protest policing / Herbert Reiter and Olivier Fillieule -- The policing of transnational protest : a conclusion / Donatella della Porta and Herbert Reiter